Social Media as a Tool for Vocabulary Learning: Reflecting on Students’ Experiences - Faruq, Salsabila; Fitriah, Fitriah (Journal of English Language and Education, 2025)
Social media today has become hand in hand with young people. It not only connects to the world but also provides learning materials including English.  This study aims to explore the use of social media as a tool to learn vocabulary by interviewing five high school students who frequently used social media as a tool for learning English vocabulary and who spent more than eight hours a week in their study.  This research found that there are seven platforms of social media that students use in learning vocabulary, such as Instagram,  TikTok, Facebook, twitter, whatsapp, discord, and YouTube. They believed that these platforms play a crucial role in their vocabulary mastery. Students gained exposure to new vocabularies and opportunities to practice them through multimodal content, varied features, and peer interaction. Another important point that the students reflect on the use of social media as a learning tool is that they have freedom to choose the content and the features which enhances their enthusiasm in learning vocabulary.